Morphological changes in the heart and aorta of rats with diet-induced metabolic syndrome - J. G. Birulina; V. V. Ivanov; E. E. Buyko; V. V. Bykov; A. N. Dzyuman; А. V. Nosarev; A. V. Grigoreva; S. V. Gusakova (Бюллетень сибирской медицины)
Aim. To identify early morphological changes in the heart and aorta of rats with experimental metabolic syndrome induced by a high-fat and high-carbohydrate diet (HFHCD).Materials and methods. The study was carried out on male Wistar rats. The animals were divided into two groups: a control group (n = 10) and an experimental group (n = 10). The rats from the control group were fed with a standard laboratory diet. The rats from the experimental group received HFHCD for 12 weeks. Body weight, blood pressure (BP), and individual parameters of carbohydrate and lipid metabolism were assessed in the rats.   A histologic examination of the heart and aorta in the animals was performed.Results. Feeding rats with HFHCD led to an increase in body weight, elevation of BP, obesity, hyperglycemia, and triglyceridemia. The histologic examination of the heart in the rats of the experimental group showed signs of vascular disease, lipomatosis, and focal myocardial degeneration. Lipid accumulation in the cells of the media, hyperplasia of adipocytes in the adventitia, and depletion and fragmentation of the elastic lamina were revealed in the aortic wall of the rats receiving HFHCD.Conclusion. The study indicated that HFHCD is an effective way to model metabolic syndrome. Structural disorders in the heart and aorta may be the mainstay for the development of cardiomyopathy and arterial hypertension in diet-induced metabolic syndrome.